2018
DOI: 10.21037/jgo.2018.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Non-surgical management of patients with intrahepatic cholangiocarcinoma in the United States, 2004–2015: an NCDB analysis

Abstract: The majority of patients with ICC in the United States continue to be managed non-surgically. RFA was associated with improved survival only in stage I disease. XRT was associated with improved survival in stage I & III disease, while RI was associated with improved survival in stage III and IV disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 17 publications
1
18
0
4
Order By: Relevance
“…In addition, after examining outcomes stratified by stage, RFA provided a survival benefit only among patients with stage I ICC (ie, solitary ICC without vascular invasion), whereas outcomes were comparable among stage II patients. This is in line with previous studies, which showed a benefit for RFA only among patients with stage I ICC . Of note, high‐dose, conformal external beam radiation therapy has recently emerged as an acceptable alternative for unresectable ICC, as it may achieve local recurrence rates similar to that of ablation especially for tumors <5 cm .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, after examining outcomes stratified by stage, RFA provided a survival benefit only among patients with stage I ICC (ie, solitary ICC without vascular invasion), whereas outcomes were comparable among stage II patients. This is in line with previous studies, which showed a benefit for RFA only among patients with stage I ICC . Of note, high‐dose, conformal external beam radiation therapy has recently emerged as an acceptable alternative for unresectable ICC, as it may achieve local recurrence rates similar to that of ablation especially for tumors <5 cm .…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with previous studies, which showed a benefit for RFA only among patients with stage I ICC. 29 Of note, high-dose, conformal external beam radiation therapy has recently emerged as an acceptable alternative for unresectable ICC, as it may achieve local recurrence rates similar to that of ablation especially for tumors <5 cm. 30 In a retrospective study of 79 patients with localized unresectable ICC, high dose (35-100 Gy) conformal external beam radiotherapy offered a median OS of 30 months, 31 whereas in a multi-institutional phase II study of 37 patients, proton-beam therapy was associated with a median and 2…”
Section: Survival Analysismentioning
confidence: 99%
“…64 A retrospective evaluation of the treatment strategies in 6,140 ICC patients diagnosed in the United States between 2004 and 2015 showed that only 29% of these patients were surgical candidates, and RFA was the only treatment strategy in the remaining patients with stage I tumors resulting in an improvement in patient survival. 65 In the cohorts undergoing surgical resection, the tumors recurred in the majority of patients despite potentially curative R0 resection. [66][67][68][69][70][71][72] In unresectable patients, the preferred chemotherapeutic regimen is a combination of gemcitabine and cisplatin, which has been shown to reach a median progression-free survival of 8 months.…”
Section: Intrahepatic Cholangiocellular Carcinomamentioning
confidence: 99%
“…[1] Liver resection (LR) is the mainstay treatment with curative intent for ICC and is associated with improved long-term survival in selected patients. [1][2][3][4] However, the prognosis after LR for ICC remains poor, and risk factors related to survival after LR have not been clearly elucidated. [5][6][7][8] For patients with hepatocellular carcinoma (HCC), liver cirrhosis (usually resulted from hepatitis B or C viral infection) has been shown to be one of the risk factors associated with poor prognosis after LR.…”
Section: Introductionmentioning
confidence: 99%